THE EFFECT OF INTEGRATION OF BATAK MUSICAL INSTRUMENTS IN STUDENT WORKSHEETS (LKPD) ON MATHEMATICAL INTERESTS OF HIGH SCHOOL STUDENTS - Panggabean, Marissa Nurianna; Simanjuntak, Ruth Mayasari; Sinaga, Rani Farida; Naibaho, Tutiarny; Simbolon, Lolyta Damora (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This study examines the influence of integrating Batak musical instruments in Student Worksheets (LKPD) on high school students' mathematical interest. The integration aims to increase students' interest in learning mathematics through a locally-based cultural approach. The research method used is quantitative with a Posttest-Only Control Group Design. The sample consists of two groups: the experimental group using Batak musical instrument-based LKPD and the control group without a similar treatment. Data were collected through a mathematical interest questionnaire and analyzed using normality tests, homogeneity tests, and t-tests. The results indicate that the data is normally distributed and there is a significant difference in mathematical interest between the two groups. Students who used the Batak musical instrument-based LKPD showed higher mathematical interest compared to the control group. In conclusion, the integration of Batak musical instruments in LKPD has a positive effect on students' mathematical interest.